Integration of Metacognition and CLIL in the First Year Engineering Classes – A Study - Gomathy , R. (International Journal of Psychosocial Rehabilitation, 2020)
A huge number of research have been made on reading strategies as it is considered as an active process to gather new information from any sort of content. Among the various strategies, metacognition (Flavell, 1985) (thinking about thinking) and its strategies is one of the processes to make reading a self regulatory learning. In this regard, general survey has been made among the first year engineering students to learn about their reading strategies. From the survey made, it is understood that they find difficult to make them comfortable and feel monotonous to do a prolonged reading and it is also understood that they are not aware of the reading strategies as they have not been encouraged to do reading from their childhood. So the researchers propose to make an analysis to find out their awareness about the strategies of Metacognition with the help of the MARSI Questionnaire (Kouider Mokhtari and Carla Reichard, 2002). Such an analysis is made to help the learners to know the metacognitive strategies which would act as Scaffolding (Vygotsky, 1978) to develop their autonomous learning to enhance their proficiency in English. The paper also gives various strategies to integrate Metacognition with CLIL in the reading classes.